Effects of Different G-Protein α-Subunits on Growth, Development and Secondary Metabolism of Monascus ruber M7 - Lei, Ming; Liu, Jiao; Fang, Yang; Shao, Yanchun; Li, Li; Yu, Jae-Hyuk; Chen, Fusheng (Frontiers in Microbiology, 2019)
Strains of Monascus filamentous fungal species have been used to produce fermented foods in Asian countries, such as China, Japan and Korea, for nearly 2,000 years. At present, their fermented products are widely used as food additives and nutraceutical supplements worldwide owing to their production of beneficial secondary metabolites. Heterotrimeric G-protein signaling pathways participate in regulating multiple biological processes in fungi. Previously, we identified three M. ruber M7 G-protein α subunits (Mga1–3) and demonstrated that Mga1 regulates growth, reproduction and some secondary metabolites’ production. Here, we systematically analyzed and compared the roles of mga1–3 by combining single- and double-gene(s) knockouts and their transcriptomic data. First, mga2 and mga3 knock-out mutants and pairwise combinations of mga1–3 deletion strains were generated, and the changes in the growth, development and the main secondary metabolites, Monascus pigments and citrinin, in these mutants were systematically compared with M. ruber M7. Moreover, RNA-Seq analyses of these mutants were performed. All three Gα subunits worked together to regulate biological processes in M. ruber M7, with Mga1 playing a major role, while Mga2 and Mga3 had supplemental roles. According to the existing literatures which we can find, gene knock-out mutants of the pairwise combination of mga1–3 and their transcriptome analysis are first reported in this study. The current results have clearly demonstrated the functional division of Mga1–3 in M. ruber M7, and could provide a deeper understanding of the effects of different Gα subunits on growth, development and secondary metabolism in other filamentous fungi.